The role of STAT6 and MEK1/2 in the M2 macrophage polarization and its impact in bone repair and inflammatory bone resorption in mice - Fonseca, Angélica Cristina (2022)
An adequate immune response is vital for proper repair. In initially pro-inflammatory aseptic lesions, it will be progressively replaced by an anti-inflammatory profile resulting in repair, however, when the aggressive agent, contaminated lesions, is of greater virulence or even the host itself is immunosuppressed, this pro-inflammatory profile remains determining. the chronicity of the lesion. Among the cells and cytokines that regulate event looping, we have macrophages, classified into M1 (pro-inflammatory) and M2 (anti-inflammatory) macrophages. Many aspects related to macrophage polarization remain unknown, and specifically thinking about the M2 polarization pathway that is widely studied in tumor models, there is a need to evaluate new models. Taking this condition to the dental field, we determined the comparison of two events that represent what was explained above, therefore, we compared the inflammatory reaction, mainly the role of M2 in post-extraction alveolar bone repair and bone degradation by periapical lesion. Bone tissue is directly affected by inflammatory events; thus, comprehensive knowledge and modulation of the immune response could allow an adequate clinical management with gain in bone volume and time in physiological or even pathological conditions. The aim of this work is to evaluate the effect generated by the pharmacological blockade of the intracellular pathways of STAT6 and MEK1/2 and its effect on different types of macrophages, interfering initially and directly in the M2 polarization process in aseptic or contaminated experimental models. For the periapical lesion model, we compared human and murine C57Bl/6-WT samples analyzed by different techniques (histology, ELISA, RT-PCR and flow cytometry) at different periods. Murine samples were further treated with STAT6 inhibitor and inoculated with CCL2p. For the post-extraction bone repair model, we used C57Bl/6-WT mice comprising a control group, transporter group, MEK1/2i group and STAT6i group analyzed by computed tomography (uCt), histological (histomorphometry, birefringence, immunohistochemistry) and molecular microscopy. Control groups, both periapical lesion and repair, did not allow confirmation of the presence of M2 macrophages (CD206, ARG, FIZZ, STAT6), which lead to an inactive periapical lesion and an adequate resolution of post-extraction bone repair, however when these cells are blocked, initially by the use of a STAT6 inhibitor, we observed that the decrease in M2 led to an active periapical lesion and a bone repair, with a little disorganization in 7 days, but that concludes satisfactorily in 14 days. Next, we follow different paths for the models. For the repair, we inhibited the MEK1/2 pathway, which is also related to M2 polarization, this inhibition most notably affected M2 migration and bone repair was more immature and delayed. For the periapical lesion model, we inoculated CCL2p which also led to an inactive lesion by the action of M2, however the combined action of CCL2p+STAT6i generated an inversion of the results. We conclude that even in a favorable environment for macrophages with an M2 profile, polarization pathways such as the STAT6 and MEK1/2 pathways are crucial and essential for the performance of these cells, and the infectious model allows us to have more robust and clear results.